2016
DOI: 10.1103/physrevb.93.165207
|View full text |Cite
|
Sign up to set email alerts
|

Self-compensation due to point defects in Mg-doped GaN

Abstract: Using hybrid density functional theory, we address point defects susceptible to cause charge compensation upon Mg doping of GaN. We determine the free energy of formation of the nitrogen vacancy and of several Mg-related defects. The entropic contribution as a function of temperature is determined within the quasiharmonic approximation. We find that the Mg interstitial shows a noticeably lower free energy of formation than the Mg substitutional to Ga in p-type conditions. Therefore, the Mg impurity is amphoter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
80
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 65 publications
3
80
0
Order By: Relevance
“…Results similar to the HSE calculations were found in other studies employing hybrid functionals. 77,78 However, V 0 N was not found to be stable in ref. 78, and the (0/−) transition level was found to occur 4 meV below the CBM in ref.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Results similar to the HSE calculations were found in other studies employing hybrid functionals. 77,78 However, V 0 N was not found to be stable in ref. 78, and the (0/−) transition level was found to occur 4 meV below the CBM in ref.…”
mentioning
confidence: 96%
“…77,78 However, V 0 N was not found to be stable in ref. 78, and the (0/−) transition level was found to occur 4 meV below the CBM in ref. 77.…”
mentioning
confidence: 96%
“…Recently this controversial discussion was revived by the results of hybrid density functional calculations of Miceli and Pasquarello [16] who concluded that "…the amphoteric nature of the Mg impurity is critical to explain the dropoff in the hole density observed experimentally": once the doping limit has been reached, additional Mg atoms are not incorporated on substitutional Ga sites any more but on interstitial sites where they form compensating double donors, thus pinning the Fermi level. The reader is referred to Ref.…”
mentioning
confidence: 99%
“…51 and 52). From the charge neutrality equations for semiconductors dominated by impurities, 54,55 we inferred that F lies at 0.16 eV below the conduction band edge. The energy profiles of the two charge states along the distortion paths are illustrated in Fig.…”
mentioning
confidence: 99%
“…Temperature-dependent entropic effects on the formation energies are negligible and can be neglected. 55 Hence, the variation of the Fermi energy destabilizes (D s 4 ) − through a rigid upwards shift of its minimum energy path. Our calculations indicate that it is sufficient to assume a downshift of the Fermi energy lower than 0.1 eV to destabilize (D s 4 ) − with respect to the (D s 4 ) 0 [cf.…”
mentioning
confidence: 99%